1965
DOI: 10.1063/1.1696447
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance Studies of Mn(CN)5NO2− and Cr(CN)5NO3− in Dilute Single Crystals

Abstract: Articles you may be interested inSinglecrystal electron paramagnetic resonance study of triplet excitons in [Fe(mesitylene)We have studied the electron paramagnetic resonance spectra of Mn(CN)oN()2-and Cr(CNhN()2as dilute solutions in single crystals of various diamagnetic hosts. From these measurements, we have obtained the spectroscopic splitting factor tensor and the hyperfine tensors to the central metal atom and nitrosyl nitrogen. In the case of Cr(CNhNOa-, we have also measured the hyperfine tensor to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1972
1972
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The high field side of the spectra for the 3A and 4A zeolites seem to indicate the existence of a strong ligand field and therefore, a low spin state of the Mn 2 + . The components of the g tensor, g = 1.965 and g ± = 2.049 for this state of Mn 2+ in the zeolite of type 3A are close to the values given by Fortman and Hayes [10]. All the measured g 0 and A 0 values and the tensor components for Mn(H 2 0)s + are given in Table 2.…”
Section: Resultsmentioning
confidence: 55%
“…The high field side of the spectra for the 3A and 4A zeolites seem to indicate the existence of a strong ligand field and therefore, a low spin state of the Mn 2 + . The components of the g tensor, g = 1.965 and g ± = 2.049 for this state of Mn 2+ in the zeolite of type 3A are close to the values given by Fortman and Hayes [10]. All the measured g 0 and A 0 values and the tensor components for Mn(H 2 0)s + are given in Table 2.…”
Section: Resultsmentioning
confidence: 55%
“…Previous investigations were mainly aimed at elucidating the mechanisms of hyperfine couplings (HFCs) at the nitrosyl N atom [1][2][3]. At the same time, the distinctive features of the behavior of the Zeeman parameters ( g -tensor components) remain poorly studied.…”
mentioning
confidence: 99%
“…At the same time, the distinctive features of the behavior of the Zeeman parameters ( g -tensor components) remain poorly studied. For instance, the EPR study revealed an abnormal value of the Zeeman parameter in a static magnetic field perpendicular to the longitudinal axis of the nitrosyl complex: > 2.0023 [1]. For oxo complexes (M is the d 1 ion and L is the ligand), the parameter is anomalous (> 2.0023 [4,5]).…”
mentioning
confidence: 99%
See 2 more Smart Citations